(3ZGjI GdeCehd aj Yde GdCUhds - (3GdMdj, GdLfGLj, GdfLaj, ef Bd cGTa GdZWGA, LYaQ Hf NVQ Hf TdGd, J (B1227 (3g`s
(3ChdgG (B:s
... (3GdHMK GdKGfj aj Mce YdI GdhVY haGFOJg aj GdehVhY dg , EYde Cf GdZQV ef GdhVY EjQGO ebGUO GdeJcde HSghdI EP dG jMUd GdYde HOhf hGSWI (B...s
(3BNQgG (B:s
... (3MjK GdNWC hMUhd GdYPQ ZjQ GdeJYeO dG jfaj NHKg hYfg GdNGeS HXghQ GdYehe (B... (3GdeUOQ GdNWC HOdjd (B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ddRQcdj (B2/124s
(3eYLe GdeDdajf (B1/491s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs